Incentive effects of self-enforcing contracts in international lending - Volker Stüven (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
The persistent debt crisis of mayor LDC-borrowers has led to various proposals on how to ease or even solve these problems. Most suggestions have in common that they concentrate on restructuring the old loans and suggest approaches to higher future lending . These proposals are based on the assumption that the debt burden accumulated in the past represents the main obstacle to new bank lending in the future. It has to be doubted, however, that debt relief in one form or another will be sufficient for generating new lending. The high debt burden constitutes only one reason for the reluctance of banks to provide fresh money voluntarily. A more fundamental reason may be related to the behavior of creditors and borrowers that lead to the present instability of the international credit market. This behavior is influenced by the institutional incentive structure prevailing in this market. New lending would, therefore, be conditional on an improved institutional framework in the international credit market.
Keywords: 330; Auslandsverschuldung; Entwicklungsländer